Pengaruh Penggunaan Media Ajar IPS Berbasis Video Interaktif Terhadap Hasil Belajar Siswa Sekolah Dasar - Irma Sofiasyari; Ike Kurniawati; Mochamad Guntur (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
The application of innovative and interactive learning media can encourage students to be active in learning. However, in reality social studies learning is still teacher-centered. The teachers do not use innovative learning media, and are fixated on one source book that has been provided by the school. This study is to determine the effect of using cultural map media on student learning outcomes on the material diversity of the Indonesian nation. The study used a quasi-experimental research method using one experimental group. Therefore, the design used by the researcher is a one group pretest-posttest design. The results of the statistical test showed that the average posttest results of the students were higher than the students' average pretest, which was 83.77 > 76.33 with Sig = 0.000. Therefore, the application of cultural map learning media has an effect on improving student learning outcomes on the material diversity of the Indonesian nation